2008
DOI: 10.1136/ard.2008.094516
|View full text |Cite
|
Sign up to set email alerts
|

Strontium ranelate reduces the risk of vertebral fracture in young postmenopausal women with severe osteoporosis

Abstract: Objectives:Early osteoporotic fractures have a great impact on disease progression, the first fracture being a major risk factor for further fractures. Strontium ranelate efficacy against vertebral fractures is presently assessed in a subset of women aged 50–65 years.Methods:The Spinal Osteoporosis Therapeutic Intervention (SOTI) was an international, double blind, placebo controlled trial, supporting the efficacy of strontium ranelate 2 g/day in reducing the risk of vertebral fractures in postmenopausal women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 17 publications
1
45
0
4
Order By: Relevance
“…This drug is atypical among osteoporosis treatments in that it both increases deposition of new bone by osteoblasts and decreases bone resorption by osteoclasts, thus favoring bone formation. The effectiveness of this drug has been demonstrated by numerous previous studies (Tournis et al, 2006;Roux et al, 2008;Seeman et al, 2008). Roux et al (2008) have reported that the risk of vertebral fractures is reduced by 35% in postmenopausal women, aged between 50 and 65 years, treated with strontium ranelate during a 4-year period.…”
Section: ؉mentioning
confidence: 89%
See 1 more Smart Citation
“…This drug is atypical among osteoporosis treatments in that it both increases deposition of new bone by osteoblasts and decreases bone resorption by osteoclasts, thus favoring bone formation. The effectiveness of this drug has been demonstrated by numerous previous studies (Tournis et al, 2006;Roux et al, 2008;Seeman et al, 2008). Roux et al (2008) have reported that the risk of vertebral fractures is reduced by 35% in postmenopausal women, aged between 50 and 65 years, treated with strontium ranelate during a 4-year period.…”
Section: ؉mentioning
confidence: 89%
“…The effectiveness of this drug has been demonstrated by numerous previous studies (Tournis et al, 2006;Roux et al, 2008;Seeman et al, 2008). Roux et al (2008) have reported that the risk of vertebral fractures is reduced by 35% in postmenopausal women, aged between 50 and 65 years, treated with strontium ranelate during a 4-year period. Similar results were reported in another study, using an older population with a mean age of 69 years, which showed that the risk of developing new vertebral fractures decreased by 41% over a 3-year period of strontium ranelate treatment, and this effect was apparent in the first year of treatment, with a 49% risk reduction (Tournis et al, 2006).…”
Section: ؉mentioning
confidence: 89%
“…During longterm treatment (4 years), strontium ranelate decreased vertebral fracture incidence by 33% 93 . Strontium also decreases the incidence of vertebral fractures by 35% in younger postmenopausal women (aged 65 or less) and by 32% in the elderly women aged 80 and over 94,95 . Strontium ranelate decreases the incidence of non-vertebral fractures by about 15% and even more (31%) in the oldest women 95 -97 .…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%
“…Many studies have shown that nanometer-controlled surfaces can influence early events such as the adsorption of proteins, blood clot formation, and cellular migration and differentiation of mesenchymal stem cells [19][20][21]. Novel drug delivery systems are being studied for the local delivery of compounds that can enhance osseointegration and bone regeneration [22].…”
Section: Maxillary Sinus Lift Using Lateral Approachmentioning
confidence: 99%